POLEN PALEOGEN-NEOGEN DARI DAERAH NANGGULAN DAN KARANGSAMBUNG JAWA TENGAH - A.A Polhaupessy (Jurnal Geologi dan Sumberdaya Mineral, 2009)
A research on palynomorph fossils is presented in this paper. Pollen samples were collected from Paleogene and Neogene rocks containing carbon materials and organic remains. The aim of this study is to better understanding the pollen distribution, age and their depositional environments as a final result. Pollen fossils from Nanggulan area suggest an age of Eocene – Oligocene, while that from Karangsambung indicates Middle Eocene – Pliocene. All of pollen, both from Nanggulan and Karangsambung were deposited in littoral environments. Keywords: Nanggulan, Karangsambung, pollen